If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3 + -1x + 4 Reorder the terms: 15 = 3 + 4 + -1x Combine like terms: 3 + 4 = 7 15 = 7 + -1x Solving 15 = 7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 15 + x = 7 + -1x + x Combine like terms: -1x + x = 0 15 + x = 7 + 0 15 + x = 7 Add '-15' to each side of the equation. 15 + -15 + x = 7 + -15 Combine like terms: 15 + -15 = 0 0 + x = 7 + -15 x = 7 + -15 Combine like terms: 7 + -15 = -8 x = -8 Simplifying x = -8
| 45+20m=30+25m | | 0.66=1.33+6x | | -7x+3=7 | | 8d-4=12 | | 0.050x^2-x+1=0 | | -18-x=-17 | | V-x-y+z=4 | | 4x=21+sqrt(56-x) | | 6x+2(5x-18)=56 | | 7z+2=23 | | 1000+100w=5000 | | D+00.2d=510 | | 15x^2+7=0 | | (2x+5)*(4x-3)=0 | | 24+4x=4x | | 10000+100w=5000 | | b=b^2 | | 2x-49=17 | | 2c^2=-3c | | 4(T-5)+2=-9+c+5 | | 2x+6=-38 | | x^2+x^2-14x-49=169 | | 6x+7(-2x-17)=-175 | | 13x^2+39x=0 | | 3(j-6)=j+10 | | (2x+8)(2x+7)= | | 3q^2-6q=0 | | 20+5x=55 | | cox(2x)-9=0 | | 2x+5=11x-4 | | 3x-4-(2x+3)=0 | | 100x=0.81 |